Exhibiting Information: Developing the Information Age Gallery at the Science Museum. - Blyth, Tilly (Information & Culture, 2016)
There is very little published literature on the display of computing technology in museums and galleries. This article reviews a variety of displays, from the early 1970s to the 1990s, to show how computing and communication technologies shifted from a taxonomic approach that inferred an element of progression to displays that take a more socially and culturally embedded approach. The article argues that by changing their focus away from computing per se to considering the history of sociocultural information networks, museum professionals can create more engaging experiences for visitors while reflecting the current concerns of the sociology of technology and historiography. Using insights drawn from the development of the Information Age gallery at the Science Museum in London, the article argues that while the shift toward information and communication networks is not without conceptual challenges, it brings to the fore the importance of infrastructure, the role of users in the coconstruction of networks, and the challenge of software in display.